Genomic Analysis for Haloacid Dehalogenase in Bacillus megaterium WSH-002 - Luqman Arif Zulkarnain; Fahrul Zaman Huyop (Journal of Tropical Life Science, 2022)
Bacterial dehalogenation is one of the processes that can reduce the environmental pollutions. The attributes of Bacillus megaterium sp. that able to grow in polluted environment suggested that, its genome contains pollutant degrading genes. To date, there were no reports related to dehalogenase in Bacillus megaterium WSH-002 and how it was regulated. Therefore, the presence of environmentally important genes that can detoxify organohalogens in many microbial genomes including Bacillus megaterium WSH-002 will be investigated. The results from genome annotations of Bacillus megaterium WSH-002 has shown its potential for bioremediation due to the putative haloacid dehalogenase proteins. Only one type of haloacid dehalogenase was identified. It was classified as haloacid dehalogenase type II because of its amino acid sequence are highly identical with HAD_type_II and HAD_L2-DEX. The study concluded that, the genome of Bacillus megaterium WSH-002 contains haloacid dehalogenase genes that is useful for biodegradation of halogenated compound. In future, further investigation on the expression of the dehalogenase gene as recombinant protein and bioinformatic analysis to study dehalogenase protein structure and functions will be considered.Ã‚Â